2016
DOI: 10.3727/096504016x14562725373798
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a Inhibits Proliferation and Enhances Chemosensitivity in Epithelial Ovarian Cancer via Reduction of SOD2

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy, accounting for 90% of all ovarian cancer. Dysregulation of miRNAs is associated with several types of EOC. In the current research, we aimed to study the role of abnormal expression of miR-146a in the development of EOC and to elucidate the possible molecular mechanisms. Compared with control samples, mRNA expression of miR-146a was significantly decreased in EOC tissues and cell lines. Overexpression of miR-146a prohibited cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Additionally, miR-146a-5p has been reported to function as a powerful inhibitor in cervical cancer [44]. Similar results have been obtained for epithelial ovarian cancer [45,46]. In this work, we found that elevated miR-146a-5p expression was indeed correlated with a better prognosis for patients with reproductive system cancers.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, miR-146a-5p has been reported to function as a powerful inhibitor in cervical cancer [44]. Similar results have been obtained for epithelial ovarian cancer [45,46]. In this work, we found that elevated miR-146a-5p expression was indeed correlated with a better prognosis for patients with reproductive system cancers.…”
Section: Discussionsupporting
confidence: 87%
“…However, the tissue samples used in the study contained various histological types of cancer (including clear cell and endometrial cancer) and the reference samples used were cultured human ovarian surface epithelial (HOSE) cells. Similarly, Cui et al (31) detected downregulation of miR-146a in OVCAR3, CAOV3 and HEY ovarian cancer epithelial cells compared with HOSE cells. To the best of our knowledge, the only previous published study investigating the differences between ovarian primary tumor and metastases in the context of miR expression levels, was performed by Vang et al (27) on 9 paired tissue specimens of primary lesions and omental metastases in serous cancer: Vang et al (27) demonstrated that miR-146a expression level was increased in metastases compared with in primary lesion tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Though the data were limited, miR‐146a expression was significantly lower in chemotherapy‐resistant patients compared to patients with partial regression or those who were in complete remission (Luo et al, ). Transfecting ovarian cancer cells with a miR‐146a mimic in tandem with paclitaxel treatment led to a more robust decrease in cell viability than with miR‐146a or paclitaxel treatment alone (Cui et al, ). Similar experiments were performed on K562 cells, a drug‐resistant CML cell line.…”
Section: Mir‐146a and Chemotherapeuticsmentioning
confidence: 99%